Effect of Dexmedetomidine on Cardiac Output among Parturient with Severe Preeclampsia after Cesarean Section. (14th April 2022) - Lv, Yanxiang; Zhou, Ying; Qiao, Yuan; Hu, Rui; Liang, Yan; Lian, Yanan; He, Tongqiang
Abstract : This study was to investigate the hemodynamic effect of dexmedetomidine among parturient with severe preeclampsia after cesarean section. Parturient with severe preeclampsia were randomly allocated to receive dexmedetomidine (0.2-0.7 μ g/kg/h) or equivalent volumes of 0.9% saline as control after cesarean section, respectively. A total of 36 parturient with severe preeclampsia were enrolled, including 18 in the dexmedetomidine (DEX) group and 18 in the saline group. Compared with the saline group, among those in the DEX group, CO was reduced by 1.30 L/min (95% CI: -2.36 to 0.25; P = 0.019 ). Additionally, HR (-13.79 bpm, 95% CI: -22.02 to -5.58; P = 0.002 ), SBP (-16.11 mmHg, 95% CI: -30.56 to -1.66; P = 0.030 ), DBP (-10.48 mmHg, 95% CI: -18.27 to -2.69; P = 0.002 ), and MAP (-12.36 mmHg, 95% CI: -22.05 to -2.66; P = 0.014 ) were reduced in the DEX group compared with the saline group. In contrast, there were no changes observed in SV and ICON between groups. In conclusion, dexmedetomidine reduces cardiac output by inhibiting the acceleration of heart rate without sacrificing myocardial contractility and stroke volume.